Psychological Wellbeing: Studi Kasus Pada Peserta Didik Yang Mengalami Burnout Di MAN 2 Kediri (Jurnal Bimbingan dan Konseling Islam, 2020)
Learners are subjects as well as objects in the learning process. In the learning process learners often get more burdens that result in a person experiencing burnout. The Burnout experienced by a person will impact on their psychic condition in their psychic. However, there are conditions where learners can receive the condition well, it is called psychological wellbeing. This research aims to know Psychological Well Being on learners who experience Burnot in MAN 2 Kota Kediri. If it is associated with burnout then, there are psychological well being links with the learners experiencing the burnout. This type of research is a qualitative study with the case study model. This research samples from grade X majoring in Science using purposive sampling. Data collection techniques conducted in the form of interviews, observations, and documentation. The results of this study are students who have psychological wellbeing tend to overcome problems in learning, cultivate self-reliance, have self-acceptance, and are able to perform their roles as well as performing the tasks as students consistently.